Floppy's phonics book 8. Stage 2, Oxford Reading Tree Phonics - Hunt, Roderick; Brychta, Alex (OXFORD UK, 2011)
Level 2 Floppy's Phonics Sounds and Letters Books show all the sounds and graphemes from Phase 3 of Letters and Sounds in the context of Oxford Reading Tree scenes, packed with activities for practice and consolidation.